Pharmacogenetics as a Future Tool to Risk-Stratify Breast Cancer Patients According to Chemotoxicity Potential from the Doxorubicin Hydrochloride and Cyclophosphamide (AC) Regimen - Esraa K. Abdelfattah; Sanaa M. Hosny; Amira B. Kassem; Hebatallah Ahmed Mohamed Moustafa; Amany M. Tawfeik; Marwa N. Abdelhafez; Wael El-Sheshtawy; Bshra A. Alsfouk; Asmaa Saleh; Hoda A. Salem (Pharmaceuticals)
Background: Studying single-nucleotide polymorphisms (SNPs) in xenobiotic-transporting and metabolizing enzyme genes before administering the doxorubicin hydrochloride and cyclophosphamide (AC) regimen may help optimize breast cancer (BC) treatment for individual patients. Objective: Genotyping specific SNPs on genes encoding for the transport and metabolism of the AC regimen and study their association with its chemotherapeutic toxicity. Method: This prospective cohort study was conducted in two hospitals in Egypt. Before receiving AC therapy, venous blood was collected from female patients with BC for DNA extraction and the genotyping of four SNPs: rs2228100 in ALDH3A1 gene, rs12248560 in CYP2C19 gene, rs1045642 in ABCB1 gene, and rs6907567 in SLC22A16 gene. Patients were then prospectively monitored for hematological, gastrointestinal, and miscellaneous toxicities throughout the treatment cycles. Results: The ALDH3A1 gene polymorphism demonstrated a significant increase in nausea, stomachache, and peripheral neuropathy among patients carrying the GC+CC genotype, compared to those with the GG genotype (p = 0.023, 0.036, and 0.008, respectively). Conversely, patients with the GG genotype exhibited significantly higher fever grades after cycles 1, 2, and 3 of the AC regimen compared to those with the GC+CC genotype (p = 0.009, 0.017, and 0.018, respectively). Additionally, fatigue severity was significantly increased among patients with the GG genotype compared to those with the GC+CC genotype following AC administration (p = 0.008). Conclusions: The SNP variation of ALDH3A1 (rs2228100) gene significantly influenced AC regimen toxicity in female BC patients. Meanwhile, SNPs in CYP2C19 (rs12248560), ABCB1 (rs1045642), and SLC22A16 (rs6907567) genes showed a significant influence on the recurrence rate of certain toxicities.